Comparative Thermal Performance Analysis of Nipah Palm Fiber and Expanded Polystyrene as Sustainable Cool Box Insulation for Small-Scale Fisheries - Lungari, Fitria Fresty; Bawias, Ishak; Tatontos, Yuliana Varala; Ingratubun, Jotje Aquarista (Department of Ocean Engineering, Faculty of Engineering, Hasanuddin University, 2026)
Small-scale fishermen in the Sangihe Islands rely heavily on expanded polystyrene (EPS) cool boxes to preserve fish during transit, yet these synthetic materials are environmentally problematic and economically limiting. This study experimentally evaluates Nipah palm fiber (Nypah fruticans), an abundant coastal biomass waste, as a sustainable insulation alternative for pumpboat-based fisheries. Three cooler box configurations were comparatively tested under controlled tropical conditions (31°C ±2°C ambient temperature) over a 12-hour period: (1) standard EPS insulation (20 mm), (2) raw compressed Nipah fiber (30 mm), and (3) a hybrid composite combining compressed Nipah fiber (30 mm) with a reflective aluminum layer. Thermal performance was assessed through continuous internal, external, and fish-core temperature monitoring at 30-minute intervals. Results demonstrate a clear hierarchy in insulation efficiency. The hybrid Nipah configuration achieved the lowest warming rate (0.167°C/hour), nearly three times slower than the EPS control. After 12 hours, the hybrid system-maintained fish temperature at 0.4°C, compared to 4.8°C in the EPS box. The improved performance is attributed to the dense lignocellulosic fiber structure, which enhances air entrapment and reduces conductive heat transfer, while the aluminum layer minimizes radiant heat gain. These findings confirm that Nipah palm waste provides a cost-effective, locally available, and environmentally sustainable insulation solution tailored to tropical maritime logistics. The adoption of Nipah-based bio-composite insulation has the potential to extend fish shelf life, reduce post-harvest losses, and decrease dependence on non-biodegradable synthetic polymers in traditional fisheries.